Exploring the perceptions of local residents regarding homelessness in the Strandfontein community - Chandler, Chernay (Department of Social Development, 2024)
This study aimed to explore the perceptions of Strandfontein residents regarding homelessness in their community. The study employed a qualitative research design, specifically an exploratory approach, through face-to-face semi-structured interviews to gain rich insights and an understanding of residents' views regarding homelessness in their community. The interviews were conducted with twenty (20) residents who have lived in the Strandfontein community for more than five (5) years. The sample consisted of fourteen (14) females and six (6) males, selected through purposeful and snowball sampling methods. The findings of the study revealed a diverse range of attitudes and beliefs among community residents regarding homelessness. Some residents demonstrated empathy, tolerance, and acceptance of homeless individuals, acknowledging the collective responsibility of the community to support people experiencing homelessness. These individuals recognised the complex societal factors contributing to homelessness. Conversely, other residents emphasised homeless individuals' responsibility. However, it was observed that participants' limited knowledge and indirect experiences, influenced by second-hand information or media portrayals, shaped their perceptions of homelessness, leading to misconceptions and biased views. Additionally, in some instances, participants attributed their perceptions to direct interactions between homeless individuals and residents. However, for most, these interactions reinforced negative stereotypes and highlighted the importance of informed and compassionate interactions. Interestingly, despite these variations in perspective, residents held contradictory views. They recognised the need to help homeless individuals while simultaneously attributing homelessness to individual choices. Furthermore, despite being open to integration, practical guidance and information on effective community engagement were lacking. Based on the study's findings and participant suggestions, several recommendations were proposed to address homelessness and foster social integration. In light of these findings, the following actions should be considered. Firstly, targeted stakeholder interventions should be implemented to address bias and attitudes towards homelessness. This can be achieved by enhancing the presence of social services within communities and promoting collaboration among stakeholders, ensuring comprehensive support and effective solutions. Furthermore, the establishment of representative community committees, with active participation from homeless individuals, can provide a platform for ongoing dialogue, problem-solving, and collective decision-making. Additionally, raising awareness and providing education to community members and homeless individuals can significantly combat misconceptions and build empathy within the community. This is done through skills development workshops and reintegration programmes.